Seroprevalence of Hepatitis C Virus in High School Students of Bangladesh - A Single Centre Study (Sir Salimullah Medical College Journal, 2022)
Introduction: Hepatitis C virus is an important pathogen due to its high prevalence and ability to cause serious complications like chronic hepatitis, cirrhosis, end stage liver disease and eventually liver cancer. Aim of this study was to Hepatitis C virus seroprevalence in the high school going children in Bangladesh.Materials and Method: It was a cross sectional study carried out in Ghior D.N. High School, Manikganj over 600 high school students within the period from April 2007 to April 2008. Two hundred students each from class VIII to X were selected. Informed written consent was taken from each students and their demographic and socioeconomic attributes, various potential parenteral exposures to blood and blood products were noted down in pre designed structured questionnaire. Venous blood of 3.0 ml was collected and was tested for anti HCV by commercial kit according to standard operating procedure. All positive cases were confirmed by ELISA method. Statistical data analysis was performed using SPSS 20.0 software. Students T test and chi-square test was done to test the significance of the factors of study in relation with the seroprevalence of anti-HCV antibodies. P< 0.05 was considered as significant.Results: The mean age of the participants was 14.6±2.26 years. Of the 600 students, 289 (48%) were male and 311(52%) were female. It was not statistically significant (P=0.089). Among the 600 students, none tested positive for hepatitis C. Of them, 60 (10.0%) belonged to upper class, 222 (37.0%) to middle class and 318 (53.0%) to lower class. Total 34 students had previous history of jaundice and 288 had previous surgeries. Both the comparison between previous jaundice with no jaundice and previous surgeries with no surgery was not statistically significant (P=0.18, 0.089).Conclusion: Prevalence of Hepatitis C is 0% in high school students in this study. Further extensive nationwide study should be carried out to determine the real scenario.Sir Salimullah Med Coll J 2022; 30: 51-54